Influence of clad layer thickness of aluminium alloy by friction surface cladding process - Nor Imrah, Yusoff; L. H., Sulaiman (Penerbit UMP, 2023)
Friction Surface Cladding (FSC) is a process that enables the deposition of clad material on a substrate through a hollow rotating tool to create thin clad layers at sufficiently high temperatures. Heat is produced during the cladding process by friction at the tool-clad layer and the substrate. This study focus on the influence of clad layer thickness of aluminium alloy AA2024 at the control process temperature around 300℃ to 350℃. The material used is AA2024-T4 for the clad layer and AA2024-T351 for the substrate. A thermal model is built using COMSOL Multiphysics 6.0 and Heat Transfer in Solid (ht) with time-dependent study is used to study the heat transformation as well as optimize the rotational speed at different clad layer thicknesses. The major finding in this study indicates that the heat generated is proportional to the clad layer thickness. The highest heat transformation can be seen at the cladding region between the cladding rod and the substrate and the temperature reaches a maximum of 333.95℃.